Separation of organic compounds and metal ions by micellar-enhanced ultrafiltration using plant-based natural surfactant (saponin) - Nita Aryanti; Aininu Nafiunisa; Vania Frimasgita Giraldi; Luqman Buchori (Case Studies in Chemical and Environmental Engineering, 2023)
A natural plant-based surfactant, saponin, was investigated for organic compound and heavy metal pollutant removal via Micellar Enhanced Ultrafiltration (MEUF) to guarantee more sustainable process. Aniline and phenol were used as the model of organic pollutant, methylene blue was selected as reactive dye pollutant, while, Zn and Cu represented heavy metal pollutant. The MEUF process using saponin was successfully removed the pollutant from the model waste water. The highest rejection of 70.76%, 81.65%, 99.95%, 99.05%, and 92.12% was achieved at the addition of 2 times CMC of saponins for removal of phenol, aniline, MB, Zn(II) ion and Cu(II) ion, respectively.